Pre-service teachers' interpretations of religious policy in citizenship education in China - Ye, Wangbei (British Journal of religious education, 2019)
Studies about religion and education in post-Mao China have become more common in recent years, but very few have touched on teacher and religious education at the basic education level. This study adopted a mixed methodology approach (questionnaire, interview and lesson design analysis) to report Chinese pre-service teachers' interpretations of religious policy in citizenship education. The analyses of the findings reveal that pre-service teachers actively constructed their understandings of religion-citizenship, rather than passively adopting the officially promoted religion-citizenship relationship.